Government Tax Regulation in the Agricultural Sector in Conditions of Import Substitution Policy - M. E. Kosov; E. V. Golubtsova; E. S. Novikova (Финансы: теория и практика)
The relevance of the research is defined by the promotion of food security improvement for Russia and the importance of government regulation in this process. The purpose of the paper is the hypothesis verification on the positive impact of the revealed methods in the government tax regulation on the national agricultural industry development in conditions of import substitution policy with further increase of food security level in the country. The task of the paper is the analysis of government regulation methods for the development of agricultural sector. Key methods of the research are the collection and analysis of statistical data, their comparative analysis, the study of normative data base in tax regulation of agricultural sector and other documents related to the food security of the country. Authors analyze the dependence of national agricultural industry on import components. Based on that the main problems of food security in the country are revealed including the low seed fund, the lack of breeding stock, the lack of veterinarian vaccines and other medicine, weak investments in fixed capital and productive capacity, the lack of research institutes and laboratories in this sector of economy. In accordance with these reasons, authors consider the tools of government regulation in the agricultural sector of economy including the tax stimulation, grants and subsidies, preferential loans and other mechanisms, which could support the effective development of national agricultural complex. The analysis of statistical data by Federal Tax Service of Russia has indicated the effectiveness of government tax stimulation of agricultural producers, which is proved by the growth of tax revenue from this category of taxpayers, despite their decrease. Researchers indicate the development of government tax regulation measures by targeted use of tax tools for the target of a decrease in the loss of tax revenue and increase investments in fixed capital in the agricultural sector.